The use of a vickers indenter in depth sensing indentation for measuring elastic modulus and vickers hardness - Adonias Ribeiro Franco Jr. (Materials Research, 2004)
Depth sensing indentation is a powerful experimental technique for determining mechanical properties of materials. In this work a computational routine was developed based on Oliver-Pharr method for measuring a more precise values of elastic modulus using a Fischerscope H100 depth sensing indentation apparatus, with a Vickers indenter. This computational routine aims also to measure Vickers hardness, as the equipment does not have software for this purpose. From indentation data it was possible to determine initial unloading stiffness, contact depth, projected contact area, reduced modulus, elastic modulus and Vickers hardness of materials. The validity of the routine was verified analyzing two coatings and nine bulk specimens with different elastic-plastic behaviors. It was verified that the elastic moduli determined through the software of the equipment resulted in great discrepancies when low loads were applied. A good estimate of the elastic moduli of the tested materials is given by the developed routine. For several testing loads, the diagonals determined by means of analytical procedure were compared with the same diagonals measured by image analysis. A good estimate of the Vickers hardness of the above-mentioned materials is given by the developed routine using different testing loads.